Curcumin in Depression: Potential Mechanisms of Action and Current Evidence—A Narrative Review - Ramaholimihaso, Tahiana; Bouazzaoui, Fayçal; Kaladjian, Arthur (Frontiers in Psychiatry, 2020)
Major depressive disorder (MDD) is one of the most prevalent and debilitating disorders. Current available treatments are somehow limited. So, alternative therapeutic approaches targeting different biological pathways are being investigated to improve treatment outcomes. Curcumin is the main active component in the spice turmeric that has been used for centuries in Ayurvedic medicine to treat a variety of conditions, including anxiety and depressive disorders. In the past decades, curcumin has drawn researchers’ attention and displays a broad range of properties that seem relevant to depression pathophysiology. In this review, we break down the potential mechanisms of action of curcumin with emphasis on the diverse systems that can be disrupted in MDD. Curcumin has displayed in a number of studies a potency in modulating neurotransmitters concentrations, inflammatory pathways, excitotoxicity, neuroplasticity, hypothalamic-pituitary-adrenal disturbances, insulin resistance, oxidative and nitrosative stress, endocannabinoid system, all of which can be involved in MDD pathophysiology. To date, a handful of clinical trials have been published and suggest a benefit of curcumin in MDD. With evidence progressively growing, curcumin appears as a promising alternative option in the management of MDD.